Crystal and Molecular Structure of Bis(2,2-diphenyl-N-(di-n-propylcarbamothioyl) acetamido)copper(II) Complex - Hakan Arslan; Ulrich Flörke; Demet Sezgin Mansuroglu (E-Journal of Chemistry)
Bis(2,2-diphenyl-N-(di-n-propylcarbamothioyl) acetamido)copper(II) complex has been synthesized and characterized by elemental analysis and FT-IR spectroscopy. The crystal and molecular structure of the title compound has been determined from single crystal X-ray diffraction data. It crystallizes in the triclinic space group P-1, with a = 13.046(2) Å, b = 13.135(2) Å, c = 13.179(2) Å, α= 67.083(4)°, β= 67.968(4)°, γ = 84.756(4)° and Dcalc =1.330 g/cm3 for Z = 2. The crystal structure confirms that the complex is a mononuclear copper(II) complex and the 2,2-diphenyl-N-(di-n-propyl-carbamothioyl)acetamide ligand is a bidentate chelating ligand, coordinating to the copper atom through the thiocarbonyl and carbonyl groups. This coordination has a slightly distorted square-planar geometry (O1-Cu1-O2: 86.48(11)°, O1-Cu1-S1: 93.85(9)°, O2-Cu1-S2: 94.20(9)° and S1-Cu1-S2: 91.21(4)°). The title molecule shows a cis-arrangement and C–O, C–S and C–N bond lengths of the complex suggest considerable electronic delocalization in the chelate rings.